Penilaian Hasil Pembelajaran Kemahiran Berbahasa Indonesia Aktif Produktif di SD Dengan Menggunakan Pendekatan Komunikatif - - Sumadi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: Since 1994 curriculum launched until now, the assessment of Indonesian teaching result should be directed to assess the student’s ability to use Indonesian communicatively in real situation, not their theoretic knowledge. But, in fact, there are still many teachers assess Indonesian teaching result from their student’s theoretic knowledge aspect, not the student’s ability to use Indonesian communicatively in real situation. It could happen because of the teacher’s understanding about the using of communicative approach in Indonesian teaching is not completely right. This article will explain the assessment of Indonesian teaching result based on communicative approach in elementary school consist of the assessment philosophy, techniques and procedures, also rubric and example test items that constructed based on communicative approach.